2018
DOI: 10.1016/j.jbo.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastases in biliary cancers: A multicenter retrospective survey

Abstract: HighlightsNatural history of biliary cancers metastatic to boneThe role of skeletal events in patients with biliary cancerBiliary cancer and bone metastases: role of bisphosphonates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…A milestone in the clinical management of skeletal related events (SRE) in cancer, including SMUP, were the discovery of bisphosphonates and SRE-directed therapies. Bisphosphonates are effective in increasing survival and reducing skeletal complications, including hypercalcemia, delaying the time of appearance of skeletal complications, and reducing bone pain in patients with metastases, particularly intravenous ones [88,89,90,91,92].…”
Section: Clinical Management For Skeletal Metastasis Of Unknown Prmentioning
confidence: 99%
“…A milestone in the clinical management of skeletal related events (SRE) in cancer, including SMUP, were the discovery of bisphosphonates and SRE-directed therapies. Bisphosphonates are effective in increasing survival and reducing skeletal complications, including hypercalcemia, delaying the time of appearance of skeletal complications, and reducing bone pain in patients with metastases, particularly intravenous ones [88,89,90,91,92].…”
Section: Clinical Management For Skeletal Metastasis Of Unknown Prmentioning
confidence: 99%
“…Another previous study found that most of the metastatic lesions from CCA had mixed osteolytic and osteoblastic patterns on the CT images (40.8%) and increased uptake on planar BS (93.6%) 4 , while another study found lytic lesions were the most common metastatic type, accounting for 57.5% of the patients. 15 Thus, the benefit of add-on SPECT/CT is still unclear and needs to be further investigated.…”
Section: Siurai N Et Al Factors Associated With Positive Bone Scan In...mentioning
confidence: 99%
“…This finding concurs with a previous study which found that bone metastasis was synchronous with visceral metastases in 48 of 137 cases (35.0%) of patients with biliary cancers. Furthermore, bone metastasis was subsequently seen in 82 patients (60.0%) who had visceral disease 15 . This finding can be explained by hematogenous spread which is the common route of metastasis to bone or other visceral organs 16 .…”
Section: Siurai N Et Al Factors Associated With Positive Bone Scan In...mentioning
confidence: 99%
“…of appearance of skeletal complications and reducing bone pain in patients with metastases, particularly intravenous ones. [78][79][80][81][82] Denosumab is a viable subcutaneous alternative and a preferred option where it is possible that it has shown moderate greater efficacy than Zoledronic acid in reducing skeletal events (excluding hypercalcemia). [83,84] Several molecules with direct or indirect effects on the bone metastases progression of solid tumors are currently investigated in several clinical trials.…”
Section: Bisphosphonates and Bone Disease Modifying Agentsmentioning
confidence: 99%